1991
DOI: 10.1002/hed.2880130208
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐2 injected around tumor‐draining lymph nodes in head and neck cancer

Abstract: Twenty patients with recurrent, inoperable head and neck squamous cell carcinoma received perilymphatic injections of natural interleukin-2 (nIL-2) for 10 days. Ten patients received 200 units (U) of nIL-2; five 1,000 U; and five 5,000 U. Irrespective of the location of the recurrence, the injections were always performed 1.5 cm below the insertion of the sternocleidomastoid muscle on the mastoid. When the ipsilateral lymphatic chain was still present, they were performed on the same side as the tumor site, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…MRs are reported for interest only, since these carcinoma recurrences progress rapidly and fail to respond to standard therapy, and are omitted in the overall evaluation of the results. All these findings are in line with those of our previous studies conducted with nIL-2 (Cortesina et al, 1988(Cortesina et al, , 1991. Unfortunately, the brief duration of all responses and the ineffective treatment of further relapses observed in this and in our previous study point to the development of resistance to IL-2.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…MRs are reported for interest only, since these carcinoma recurrences progress rapidly and fail to respond to standard therapy, and are omitted in the overall evaluation of the results. All these findings are in line with those of our previous studies conducted with nIL-2 (Cortesina et al, 1988(Cortesina et al, , 1991. Unfortunately, the brief duration of all responses and the ineffective treatment of further relapses observed in this and in our previous study point to the development of resistance to IL-2.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that a biological therapy was also able to induce 12 MRs is a further point of interest. Our previous findings with nIL-2 (Cortesina et al, 1988(Cortesina et al, , 1991 and present findings with rIL-2 display some common features: good susceptibility on the part of small recurrences in the primary tumour site, especially the oropharynx; the absence of side-effects; the functional effectiveness of the administration route; and the inverse proportion between tumour mass and clinical response. These features suggest that small primary head and neck tumours before surgery and the minimal residual disease that follows surgery are more suitable settings for locoregional immunotherapy.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…There have been previous reports of local thrombus associated with intraarterial IL-2 (Klasa & Silver, 1989;Eggermont et al, 1990;Mavligit et al, 1990) and it has been suggested that this is due to direct damage to the vascular endothelium by IL-2 activated lymphocytes (Damle et al, 1987), activation of the intrinsic system of coagulation (Fleischmann et al, 1991) or an increase in the coagulant properties of endothelium by IL-2-induced cytokines such as IL-1 and tumour necrosis factor (Cotran & Pober, 1989). Phase II trials in patients with squamous cell carcinoma of the head and neck utilising perilymphatic injections have been performed but reported response rates vary widely, from 0-8% (Selvaggi et al, 1990;de Mulder et al, 1989) to 65% (Cortesina et al, 1991). All these studies suggested that systemic toxicity is absent when this approach is employed, but at doses of 103 iu local swelling and pain occurred similar to that observed in our patients (Cortesina et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Phase II trials in patients with squamous cell carcinoma of the head and neck utilising perilymphatic injections have been performed but reported response rates vary widely, from 0-8% (Selvaggi et al, 1990;de Mulder et al, 1989) to 65% (Cortesina et al, 1991). All these studies suggested that systemic toxicity is absent when this approach is employed, but at doses of 103 iu local swelling and pain occurred similar to that observed in our patients (Cortesina et al, 1991). In these studies bolus doses were given and thus the tumour infiltrating lymphocytes were only intermittently exposed to IL-2.…”
Section: Discussionmentioning
confidence: 99%